Management of acute pain in the postoperative setting: the importance of quality indicators. (2nd January 2018) - Meissner, Winfried; Huygen, Frank; Neugebauer, Edmund A.M.; Osterbrink, Jürgen; Benhamou, Dan; Betteridge, Neil; Coluzzi, Flaminia; De Andres, José; Fawcett, William; Fletcher, Dominique; Kalso, Eija; Kehlet, Henrik; et al.
Abstract: Despite the introduction of evidence-based recommendations for postoperative pain management (POPM), the consensus is that pain control remains suboptimal. Barriers to achieving patient-satisfactory analgesia include deficient knowledge regarding POPM among staff, lack of instructions, insufficient pain assessments and sub-optimal treatment. Effective monitoring of POPM is essential to enable policy makers and healthcare providers to improve the quality of care. Quality indicators (QIs) are quantitative measures of clinical practice that can monitor, evaluate and guide the quality of care provided to patients. QIs can be used to assess various aspects relating to the care process and they have proven useful in improving health outcomes in diseases such as myocardial infarction. In this commentary we critically analyze the evidence regarding the use of QIs in acute POPM based upon the experience of pain specialists from Europe and the USA who are members of the Change Pain Advisory Board. We also undertook a literature review to see what has been published on QIs in acute pain with the goal of assessing which QIs have been developed and used, and which ones have been successful/unsuccessful. In the hospital sector the development and implementation of QIs is complex. The nature of POPM requires a highly trained, multidisciplinary team and it is at this level that major improvements can be made. Greater involvement of patients regarding pain management is also seen as a priority area for improving clinical outcomes. Changes in structure and processes to deliver high-level quality care need to be regularly audited to ensure translation into better outcomes. QIs can help drive this process by providing an indicator of current levels of performance. In addition, outcomes QIs can be used to benchmark levels of performance between different healthcare providers.